Risk Factors, Complications, and Treatment Modalities for Sudden Sensorineural Hearing Loss in Pregnant Women: A Systematic Review and Meta-analysis - Haibin Qian; Huaqin Yang (Noise and Health)
Background: Sudden sensorineural hearing loss (SSNHL) during pregnancy is a rare condition and has not been much studied. The study aimed to perform a systematic review and meta-analysis of the risk factors, complications, and treatment modalities for SSNHL in pregnant women. Materials and Methods: PubMed, Web of Science, Scopus, ProQuest, and Google Scholar were used for the literature search. The Cochrane technique for assessing risk of bias was used for the article quality appraisal, and RevMan 5.4 was used for conducting the meta-analysis. Standard mean difference (SMD) and odds ratios with a 95% confidence interval (95% CI) were utilized. Heterogeneity and publication bias were assessed using the I-square (I2) test statistic and the Egger’s test, respectively. Results and Discussion: The seven primary studies employed prospective and retrospective study designs. The meta-analysis showed that there were fewer risk variables for SSNHL in the experimental group compared with those in the control group (SMD = −0.45 to 3.24, 95% CI = −3.063.63 to 2.16–2.85), indicating that the analysis revealed an insignificant difference. However, the treated patients presented hearing improvement, suggesting a significant analysis (SMD = −0.6710.20, 95% CI = −1.2713.51 to −0.066.88). Furthermore, after therapy, substantial differences were observed in SMD between the two groups (SMD = −0.7415.18, 95% CI = −1.2423.85 to −0.256.40) in favor of the experimental group patients, based on the analysis results of four included studies. However, the I2-value of 0% showed that the heterogeneity was low. Conclusion: SSNHL during pregnancy is a notably rare condition with an unknown cause. However, hormonal fluctuations, particularly increased levels of estrogen and progesterone during pregnancy, have been frequently implicated as potential triggers for SSNHL.